STEAM Education: Technological Skills, Students' Cultural Background and Covid-19 Crisis - Dana-Picard Thierry; Hershkovitz Sara (De Gruyter, 2020)
We present an initial description of an ongoing research project. Students are attracted to learn mathematics, not only for its application but also for their cultural interest. The students' cultural backgrounds are used, and situations are analyzed and modeled using technology. This first step has been instrumental in making the transition to distance learning necessary due to the Covid-19 crisis. We focus on a specific population of students who had to overcome, within a short time, two important transitions in the learning processes.